دور القلب في العملية التفكيرية من المنظور الإسلامي: دراسة وصفية تحليلية (The Role of the Heart in the Thinking Process: An Analytical Study) - بادي, جمال أحمد بشير; شوشة, حسام موسى (Journal of Islam in Asia (E-ISSN 2289-8077), 2018)
مع قرار الجامعة الإسلامية العالمية بماليزيا بأن تكون مادة التفكير الإبداعي متطلبا جامعيا بحلول العام الجامعي ٢٠١٨/٢٠١٩م، تصبح الحاجة ملحة للقيام بدراسات بحثية حول موضوع "التفكير وقضاياه ومفاهيمه" من منظور إسلامي. ومع تقدم العلوم والمعارف ظهرت بعض الدراسات المعاصرة التي تبيًن جوانب مهمة لدور القلب في العملية التفكيرية. ويهدف البحث لإبراز معالم دور القلب في العملية التفكيرية في ضوء نصوص القرآن الكريم واستقراء بعض أقوال العلماء الواردة في دلالاتها لتجلية معانيها. الكلمات المفتاحيّة: التفكير، القلب والتفكير، القلب في القرآن، العقل والقلب. Abstract With the decision of the International Islamic University Malaysia to offer Creative Thinking subject to all its students as a university requirement (UNGS) starting semester I of the new academic year 2018/2019, it becomes vital to have more research work on thinking its concepts and issues from an Islamic perspective. With knowledge advancement, a number of studies showed the importance of the role of the heart in thinking process. The paper aims at exploring different aspects of heart’s role in cognition in the light of the Quranic verses’ texts and its scholarly interpretations, implications and connotations. Keywords: thinking, heart and thinking, heart in the Quran, the heart and mind.